Effectiveness of Sustainable Urban Projects in the city of Baghdad - Wadhah Abdul sahib Hussein; Zaynab Radi Abaas (Iraqi Journal of Architecture and Planning, 2018)
Â This research comes in an attempt to evaluate and compare between the efficiency of a selected sustainable urban projects from Baghdad city (Al Adhamiya and Al Kadhimiya areas) through applying the criteria ofurban sustainability and compared using SWOT analyses model(represents one strong word: S = strengths, W = weaknesses, O = opportunities, T = threats.), this done by examine the most important strategies which targeted to extrapolate the urban form as a vital sustainable structure, and has become a standard which could measure and evaluate the impact of the application for sustainable criteria. These strategies know as Smart Growth Strategies which include, Development, Design, Transportation, Open & Natural Space Protection, Open Space Creation, Sense of Place, and Urban Community Strategies. Here this search tries to extract the most local standards that consistent with the nature and environment of sustainable urban Iraqi projects in general and Baghdad in particular by reviewing the Smart Growth principles and strategies. However, the aim is to determine the effectiveness and the successfulness of the adopted urban projects in Baghdad in applying the urban sustainability criteria in the one hand, and to extract the most important positive points which serve the local environment and utilize them to establish the foundations for possible urban standards adopted in the evaluation of sustainable urban future projects on the others. Therefore, the most important findings in this research is the possibility of evaluate the performance of sustainable urban projects using SWOT analyses model through examining the internal environment which represented by the Strengths and Weaknesses of each project and external environment which represented by the Opportunities and Threatens of the economic situation, social life and environmental conditions. In conclusion, the search developed a local, comprehensive checklist which adopts the urban sustainability standards in the one hand, and at the same time, it can be used and developed to evaluate the performance of future urban sustainable development projects.